2014
DOI: 10.1136/bcr-2013-202051
|View full text |Cite
|
Sign up to set email alerts
|

Primary low-grade diffuse small lymphocytic lymphoma of the central nervous system

Abstract: A 45-year-old Indian woman presented in neurosurgery outpatient with seizures, headache and vomiting for the past 1 month. MRI of the brain was suggestive of a malignant central nervous system (CNS) tumour. Histological and immunohistochemical examinations of stereotactic biopsy of the tumour were diagnostic of a low-grade diffuse small lymphocytic lymphoma of the CNS. No evidence of any occult systemic lymphoma was observed, confirming its ‘primary’ origin in the CNS. The diagnosis of a low-grade primary CNS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“… Bcr-2013-202,051. 37 45 F Seizures, headaches, and vomiting NA NA NA NA Biopsy Surgical excision RT Relapse Clin Lymphoma Myeloma Leuk. 2013.13.…”
Section: Discussionmentioning
confidence: 99%
“… Bcr-2013-202,051. 37 45 F Seizures, headaches, and vomiting NA NA NA NA Biopsy Surgical excision RT Relapse Clin Lymphoma Myeloma Leuk. 2013.13.…”
Section: Discussionmentioning
confidence: 99%
“…Primary CNS SLL is extremely rare. By review of the literature, only two cases of primary SLL involving the brain parenchyma and dura have been reported so far [5, 6]. In this study, for the first time, we reported two cases of primary SLL located in the bilateral ventricles with identical clinical presentations, neuroimaging features, pathological results and prognoses.…”
Section: Discussionmentioning
confidence: 60%
“…To gain further insight into the occurrence of low grade B-cell lymphomas and their association with the formation of CNS amyloidomas, we performed a literature search of the PubMed database for primary CNS small low grade B-cell lymphoma. Our search identified 12 cases of primary CNS lymphoplasmacytic lymphoma [ 2 , 8 – 10 ], one large case series with 69 cases of primary CNS marginal zone lymphoma (MZL) [ 11 ], one case of primary CNS follicular lymphoma [ 12 ], and one case of primary CNS small lymphocytic lymphoma (SLL) [ 13 ]. Among these cases, we found 5 cases of primary CNS low grade small B-cell lymphomas that presented in association with intracerebral AL amyloid deposition [ Table 1 ].…”
Section: Discussionmentioning
confidence: 99%